Increased inflammatory response in patients with dilated cardiomyopathy is associated with dyslipidemia: Effects of statin therapy - Iakovis, P; Anyfantakis,Z.A.; LIMAS, C; Kroupis, C.; Degiannis, D.; Cokkinos, D.V. (Angiology, 2011)
Dilated cardiomyopathy (DCM) is associated with increased inflammatory response reflected among other markers in high-sensitivity C-reactive protein (hsCRP) and soluble interleukin-2 receptor (sIL-2R) levels. We examined prospectively 60 consecutive patients with DCM. Of them, 30 were dyslipidemic (group I) and 30 normolipidemic (group II). Group I patients were randomized to either simvastatin therapy (20 mg/day, group Ia, n = 15) or hypolipidemic diet therapy (group Ib, n = 15). Patients were re-evaluated 6 months later. High-sensitivity C-reactive protein and sIL-2R levels were significantly higher in group I compared with group II patients (19.5 +/- 3.4 vs 3.03 +/- 3.5 mg/L, P = .01, 1137 +/- 441 vs 599 +/- 235 pg/mL, P = .001, respectively). There was a significant correlation between sIL-2R and hsCRP levels in dyslipidemic patients but not in normolipidemic patients. Significant reduction of hsCRP and sIL-2R levels was observed only in group Ia patients. Patients with DCM having dyslipidemia have increased inflammatory response, which is reduced after 6 months of statin therapy
DA - 20101207 IS - 1940-1574 (Electronic) IS - 0003-3197 (Linking) LA - eng PT - Journal Article PT - Randomized Controlled Trial RN - 0 (Hydroxymethylglutaryl-CoA Reductase Inhibitors) RN - AGG2FN16EV (Simvastatin) SB - IM
Keywords: Cardiomyopathy,Dilated; Complications; Drug Therapy; Dyslipidemias; Etiology; Female; Greece; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Inflammation; Male; Middle Aged; Prospective Studies; Simvastatin; therapeutic use; therapy